EVALUATION OF SEX-SPECIFIC DIFFERENCES OF ANTHROPOMETRIC PARAMETERS OF GROWTH IN 9 -YEAR-OLD MACEDONIAN CHILDREN FROMURBANAREA - Zafirova Biljana; Lazarova D; Trpkovska B; Cadikovska E; Bundovska S; Bojadgieva B (Macedonian Association of Anatomists and Morphologists, 2014)
Aim: Evaluation of sex-specific differences of anthropometric parameters that were used as indicators for growth in children at the age of 9 years. Subjects and methods: The study included 225 healthy children aged 9 years from Macedonian nationality and urban area. Fourteen anthropometric parameters were measured that define longitudinal, circular and transversal parameters of the skeleton using standard equipment and measurement technique. The following indicators were calculated: weight-for-age [BW], height-for-age [BH] and BMI. Results: The majority of anthropometric parameters showed no significant sex-specific differences, with exception of diameter of wrist, and circumferences of head, chest, and upper-arm, which were significant in favour of boys. Values of the 50th percentile in boys were as follows: 34.4kg for BW, 136.7 cm for BH and 18.25 kg/m2 for BMI. The values of these parameters in girls were: 32.25 kg for BW, 133.05cm for BH and 18 kg/m2 for BMI. Conclusions: These results can be used as criteria for the assessment of the anthropometric characteristics and detection of deviations in growth and nutritional status in 9-year-old children.
Keywords: anthopometry; growth; children